TWO-DIMENSIONAL LEASE CONTRACT WITH PREVENTIVE MAINTENANCE USING BIVARIATE WEIBULL - Husniah, Hennie -; Maulana, Hutomo Atman; Pasaribu, Udjianna S; Iskandar, Bermawi P (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
This paper develops a two-dimensional lease contract for repairable products. During the contract period, all maintenance actions are carried out by the lessor. There are two customer types considered – the one whose lease contract end because a usage limit and the other type whose lease contract cease because the time limit has reached ﬁrst. The proposed model uses a two-dimensional approach, and model failures using a bivariate Weibull distribution. When the age or usage of equipment reaches a speciﬁed limit, an imperfect preventive maintenance is conducted and each PM will reduce the failure rate level of the equipment. Furthermore, if the equipment fails, a minimal repair corrective maintenance is performed. As an illustration, a numerical example is presented to show the optimal preventive maintenance that minimizes lessor’s maintenance cost, and the expected number of breakdowns during leased contract period. This proposed model will be compared with a recent relevant approach through numerical computation.